Music, wit, and wisdom: The autobiography of Artur Schnabel - Schnabel, Artur 1882-1951; Matheson, Lynn; Grünzweig, Werner (Hofheim Wolke Verlag, 2009)
The twelve lectures held by Artur Schnabel at the University of Chicago in 1945 are generally thought of as his autobiography. This new edition of the book My Life and Music is a complete revision of the previously published text, with considerable additions to some sections. The text was revised using the lecture manuscripts stored in the music archives of the Akademie der Künste, Berlin.Schnabels autobiography can still be read today as a key work of 20th century music history. His dazzling intellect, profound humour and acute insights into music and musical life make his lectures as relevant today as they were at the time. Schnabel was an artist who reflected upon the value of music in modern society like no other practicing musician, and who foresaw developments decades ago that are only now becoming fully apparent.